Electric ducted fan controller and self-balancing system for two-wheeler motorbike - Horoub, Mamon; Alzaydi, Ammar; Hanieh, Ahmed Abu (Frontiers in Mechanical Engineering, 2023)
A new method of achieving self-balancing for two-wheeled vehicles is described in this paper. The structure is characterized by the presence of two electric ducted fans which are designed to blow air in the opposite direction of the fall in order to maintain equilibrium. Due to their ability to move in two degrees of freedom, Electric Ducted Fans motors are able to propel and lower the weight of the two-wheeler while remaining stable. It is described how the Proportional-Integral-Differential arducopter controller works, which employs an Inertial Measurement Unit sensor and a nonlinear complementary filter on particular orthogonal arrangements to determine the lean angles at any specific time, as well as a feedback loop to maintain the system at the required upright 0° lean angle at all times. Following that, the proposed Proportional-Integral-Differential controller is tested on a small-scale model in order to verify the proposed idea of self-balancing using Electric Ducted Fans motors. Mathematical modeling for the small-scale model has been calculated. Then the response of the Proportional-Integral-Differential controller for lean angle against external disturbances is tested theoretically and experimentally. After obtaining positive outcomes on the small-scale model, the concept that has been suggested is evaluated versus a large-scale design (motorbike) by constructing the mechanical and electrical components. The process breaks down into three primary phases: design and fabrication of mechanical parts, design of electrical components, and design of control systems. The innovative aspect of this work is the introduction of a method for achieving self-balancing in two-wheeled vehicles using electric ducted fans.